2006
DOI: 10.1051/animres:2006040
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive abilities of the females and sustainability of ruminant livestock systems. A review

Abstract: -In a systemic approach, the breeder can be considered as the decisional component of the livestock system, whereas animals are usually depicted to be part of its biotechnical component. The animal itself is a biological system whose ability to survive, grow, reproduce and cope with the environnement and livestock practices play a major role in the ability of the livestock system to sustain. In such a conceptual representation of the system, the reproductive females draw a peculiar attention since they determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(52 citation statements)
references
References 47 publications
3
43
0
3
Order By: Relevance
“…The present study indicates that the superiority of CR over PU cows was associated with a better metabolic status (greater BCS, serum insulin and hepatic GHR mRNA abundance) particularly in late fall (−165 days) and with greater hepatic IGFBP3 mRNA expression in late winter (−75 and −45 days) and in early lactation (+15 days). These results would support the concept of a 'metabolic memory' impacting reproduction, allowing nutritional information to be carried forward beyond the life of the original metabolic stimulus (Blanc et al, 2006) …”
Section: Hepatic Expression Of Somatotropic Axis Genessupporting
confidence: 57%
“…The present study indicates that the superiority of CR over PU cows was associated with a better metabolic status (greater BCS, serum insulin and hepatic GHR mRNA abundance) particularly in late fall (−165 days) and with greater hepatic IGFBP3 mRNA expression in late winter (−75 and −45 days) and in early lactation (+15 days). These results would support the concept of a 'metabolic memory' impacting reproduction, allowing nutritional information to be carried forward beyond the life of the original metabolic stimulus (Blanc et al, 2006) …”
Section: Hepatic Expression Of Somatotropic Axis Genessupporting
confidence: 57%
“…In addition, numerous transfers of improved dairy cattle from temperate zones to harsh environments revealed that performance were considerably lower due to the recognized effects of genotype-environment interactions (Hammami et al, 2008). The approach to analysing the exact causes of difficulties encountered with highly selected ruminants, even in ICs, is now questioned (see Blanc et al, 2006;Friggens and Newbold, 2007;Friggens et al, 2010).…”
Section: Effects Of Feeding Practices In Producing Animalsmentioning
confidence: 99%
“…Several functional responses of ruminants to underfeeding constraints have been described and classified according to the shape of the response curves (Blanc et al, 2006;Friggens and Newbold, 2007). In the case of domestic ruminants their adaptive response cannot be assessed only by the individual capacity of survival or even by the species perennity but, importantly, by the ability to sustain a given productive function.…”
Section: Effects Of Feeding Practices In Producing Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the herd or flock has to face alternative periods of low and high feed availability, the production cycle is secured by two well-known mechanisms: the mobilization and reconstitution of body reserves and the adjustment of animal performance, milk production for the lactating females or growth rate for the young (Blanc et al, 2006). In Lebanese Baladi dairy goats, each time the feed availability increases (i.e.…”
Section: Animal and Herd Behaviour In Mediterranean Rangelandsmentioning
confidence: 99%